The Book of Samuel and its response to monarchy - Kipfer, Sara; Hutton, Jeremy M. (Kohlhammer Verlag, 2021)
Cover sheet -- Front page -- Imprint -- Contents -- Preface -- The Book of Samuel and Its Response to Monarchy - An Introduction -- 1. The Book of Samuel as a Text Collection about Different Stages of the Institutionalization of Power -- 2. The Book of Samuel as a Medium of Power Communication and a Contribution to the Political Discourse Through the Centuries -- 3. Conclusion -- Bibliography -- Hannah's Prayer as Hope for and Critique of Monarchy -- 1. Introduction -- 2. Hannah's Prayer in the Final Form of Samuel -- 3. Hannah's Prayer as a Discrete Text -- 4. Hannah's Prayer as an Embedded Text -- 5. Hope for and Critique of Monarchy -- 6. Conclusion -- Bibliography -- Images by and Images of Philistia: Winner and Loser Perspectives in 1 Samuel 5-6 -- 1. The Ark in Philistia: Act I (1 Sam 5:6-12) -- 1.1 The Embedded Direct Speeches -- 1.2 The Narrative Parts -- 2. The Ark in Philistia: Act II (1 Sam 6:1-*18) -- 2.1 The Embedded Direct Speeches -- 2.2 The Narrative Parts -- 3. Images by Philistia -- 4. Images of Philistia: Conclusion -- Bibliography -- Remembering Kingship: Samuel's Contributions to Postmonarchic Culture -- 1. On Kings, Anthropology, and Ancient Judean Literature -- 2. On History, Theory, and Method -- 3. On Governments and Dynasties, Divine Choices and Promises, Samuel Being Stuck in the Middle -- 4. On Remembering Monarchy with and through Samuel -- Bibliography -- Tribal Contentions for the Throne: A Culturally Enthused Suspicious Reading of 1 Samuel 1-8 -- 1. Introduction -- 2. Born a Leader or Destined to Lead: Samuel's Birth Narrative and Tribal Contentions for Judgeship or Kingship -- 2.1 Samuel's Birth Narrative (1 Samuel 1-2) within the frame-work of contention for power -- 2.2 Eli-Samuel/Levi-Ephraim -- 3. Kingship is Fought for: Contests for Kingship -- 3.1 Samuel-Saul/Ephraim-Benjamin Contention.
Description based on publisher supplied metadata and other sources
Keywords: Bible -- Samuel -- Criticism, interpretation, etc; Bible; Bible - Criticism, interpretation, etc; Israel; Aufsatzsammlung; König; Bibel / Samuel; Monarchie